Ideology and Power in Political News Text: Appraisal in Critical Discourse Analysis - Cahyono, Setyo Prasiyanto; Areni, Galuh Kirana Dwi; Sumarlam, Sumarlam (Universitas Negeri Semarang, 2021)
This study attempts to reveal the ideology and power expressed in the news text entitled Ã¢â‚¬Å“The burning scar: Inside the destruction of AsiaÃ¢â‚¬â„¢s last rainforestÃ¢â‚¬Â. The data of this study were obtained from one of the most famous online Newspapers namely BBC. Whilst, in doing the critical analysis, systemic functional linguistics specifically the use of appraisal proposed by Martin and White (2005) was applied to find out the ideology as well as the power of the text. The findings show that there are three appraisal items found such as attitude, engagement, and graduation simultaneously. Affect is the most dominant appraisal found in the text. It represents the feelings of the people who live in Papua where their land has been destroyed by the world's largest exporter of palm oil from South Korea. Besides, they also criticize the Indonesian government which sold their land to the company without any notice to the tribe who live there. Then, engagement represents the tribeÃ¢â‚¬â„¢s voices where they have to move from their land. The last is graduation which represents the tribeÃ¢â‚¬â„¢s experience when they were kicked out from their land. Meanwhile, the ideology of the text is represented by the use of attitude consisting of affect, appreciation, and judgment. Furthermore, the power deals with the tribeÃ¢â‚¬â„¢s tenor such as contact, status dan affect.Ã‚Â